The six conventions of corporate branding. - Knox, Simon; Bickerton, David (Emerald Group Publishing Limited, 2003)
This paper considers the emerging focus in both academic and practitioner literature on the concept of the corporate brand and argues that the underlying generative mechanisms and processes that enable successful corporate brand management are not clearly understood. Based on the findings of recent fieldwork, the authors outline six new conventions for understanding the processes of nurturing and managing a corporate brand and discuss the implications of these conventions for the emergent theory of corporate brand management. Evidence from this work has also led the authors to propose a more holistic definition of the corporate brand, "the visual, verbal and behavioural expression of an organisation's unique business model".
Keywords: Convergence in corporate branding; action research and intervention; the six conventions of corporate brand management